Dye-surfactant interaction in the premicellar region - (:unkn) unknown (AMER OIL CHEMISTS SOC A O C S PRESS, 2003)
The interaction of safranin-O (SO), a cationic dye, with anionic surfactants [sodium dodecylsulfate (SIDS) and sodium dodecylsulfonate (SDSo]) having the same hydrophobic group but different polar groups was studied spectrophotometrically in the premicellar region far below the critical micelle concentration in aqueous media using the method of continuous variations, also called Job's Method. This method was applied to determine the equilibrium complex formation constant (K) as well as the molecular complex formation ratio. Both SDS and SDSo formed stable associations with SO, and the molecular complex formation ratio was determined as 1:1. The data obtained from Job's Method indicated that the equilibrium complex formation constant of SDS is higher than that of SDSo. We also studied the influence of cosolvents such as methanol, dimethylformamide (DMFA), and dioxan (DX) on molecular complex formation between SDS and SO, and observed that the presence of cosolvents inhibited molecular complex formation. This inhibitory effect of cosolvents on molecular complex formation followed the order of methanol > DMFA > DX.
Keywords: anionic surfactant; cationic dye; complex formation; cosolvent; dye-surfactant interaction; Job's Method; premicellar region; safranin-O; AMPHIPHILIC HEMICYANINE DYES; SODIUM DODECYL-SULFATE; MICELLAR SOLUTIONS; ANIONIC SURFACTANTS; ALCOHOLS; SYSTEMS; BROMIDE; ASSOCIATION; STABILITY; ORANGE